Analisis Media Sosial Instagram Dan Suasana Cafe Terhadap Kepercayaan Konsumen Di Era New Normal (Survei Pada Followers Instagram Industri CafÃ© Palabuhanratu) - Ce Mutia Izmilla; Asep Muhammad Ramdhan; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between Instagram social media and cafe atmosphere on consumer trust in the new normal era. The method used by the researcher is descriptive associative and distributing questionnaires with a sample of 327 respondents at the Followers cafe industry in Palabuhanratu. Researchers used data analysis techniques, namely multiple linear regression assisted by SPSS 24 software. The results of the research studied by researchers can show that Instagram social media and cafe atmosphere affect consumer confidence. Keyword : Social Media Instagram, Store Atmosphere, Coustumer Trust